1994
DOI: 10.1128/jvi.68.5.3000-3006.1994
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human antibody responses to four corners hantavirus infections among patients with hantavirus pulmonary syndrome

Abstract: Hantavirus pulmonary syndrome (HPS) is a human disease caused by a newly identified hantavirus, which we will refer to as Four Corners virus (FCV). FCV is related most closely to Puumala virus (PUU) and to Prospect Hill virus (PHV). Twenty-five acute HPS serum samples were tested for immunoglobulin G (IgG) and IgM antibody reactivities to FCV-encoded recombinant proteins in Western blot (immunoblot) assays. All HPS serum samples contained both IgG and IgM antibodies to the FCV nucleocapsid (N) protein. FCV N a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(72 citation statements)
references
References 27 publications
6
65
0
1
Order By: Relevance
“…IgG antibodies against N develop early after onset of symptoms and persist in serum for years, whereas a slower IgG response against the glycoproteins has been described earlier using EIA [Lundkvist et al, 1993;Vapalahti et al, 1995]. In other studies, the G1-antibody responses have been shown to become detectable in the acute phase of hantavirus pulmonary syndrome, but not of PUUV or Hantaan virus infections when recombinant G1 antigens expressed in bacterial or yeast systems were used [Jenison et al, 1994;Hjelle et al, 1997]. In some reports, an early antibody response to PUUV-G1 has been shown, G2 antibodies appearing later according to inhibition EIA or slot-blot assay/ EIA [Go Ètt et al, 1997].…”
Section: Introductionmentioning
confidence: 78%
“…IgG antibodies against N develop early after onset of symptoms and persist in serum for years, whereas a slower IgG response against the glycoproteins has been described earlier using EIA [Lundkvist et al, 1993;Vapalahti et al, 1995]. In other studies, the G1-antibody responses have been shown to become detectable in the acute phase of hantavirus pulmonary syndrome, but not of PUUV or Hantaan virus infections when recombinant G1 antigens expressed in bacterial or yeast systems were used [Jenison et al, 1994;Hjelle et al, 1997]. In some reports, an early antibody response to PUUV-G1 has been shown, G2 antibodies appearing later according to inhibition EIA or slot-blot assay/ EIA [Go Ètt et al, 1997].…”
Section: Introductionmentioning
confidence: 78%
“…High titers of IgM and IgG antibodies against hantavirus N and Gn proteins are detectable in the sera of patients during the acute phase, enabling reliable serological confirmation of infection (Bostik et al, 2000;Elgh et al, 1997;Groen et al, 1994). SNV Gn antibodies are highly specific and do not cross-react with Gn antigens of other hantaviruses Jenison et al, 1994). The most widely used serological tests for diagnosis of HCPS are IgM capture and IgG indirect ELISAs (Li et al, 2002).…”
Section: E Diagnosismentioning
confidence: 99%
“…The deletion-mapping technique defines a segment of gB-2 that contains one or more linear antibody-binding sites but does not define the minimum epitope recognized by those antibodies. This strategy has been used extensively by our group to localize human antibodyreactive segments of the Four Corners hantavirus and human papillomavirus antigens (29)(30)(31)(32)59).…”
Section: Discussionmentioning
confidence: 99%